Food and feeding habits of the croakers,'Otolithes ruber'(Schneider) Pennahia macrophthalmus (Bleeker) and Johnius belangerii (Cuvier),(Pisces:Sciaenidea) - Komathi Kolandai (Universiti Pertanian Malaysia, 2012)
Qualitative and quantitative analysis carried out on the stomach contents of the three sciaenids and revealed that they are carnivorous subsisting primarily on shrimps and secondarily on fishes.